The Nontraditional Role of Pharmacists After Hurricane Katrina: Process Description and Lessons Learned - Hogue, Michael D. (Association of Schools of Public Health, 2009)
In the week before Hurricane Katrina's landfall in August 2005, emergency management officials in Jefferson County (Birmingham), Alabama, began to make plans for the potential influx of evacuees from the Gulf Coast. No pharmacy component to the plan was in place at that time. The Jefferson County Department of Health (JCDH) discovered that local pharmacies and hospital emergency departments were dealing with significant requests for medication refills. JCDH, in cooperation with a local school of pharmacy, developed a plan for addressing the unforeseen need for routine prescription refills by evacuees. This article discusses this novel pharmacy plan and lessons learned from the event, and may serve as a model for other municipalities and/or states interested in preparing a pharmacy response to future natural disasters.